Prevalence of Color Vision Defect in Bachelor of Dental Surgery Students at Kathmandu Medical College - Lohani, Junu; Shrestha, Lajana; Adhikari, Ram Kumar; Dhakal, Sampada (Journal of Nepalese Prosthodontic Society, 2025)
Introduction: Color vision plays a vital role in prosthodontics and aesthetic dentistry, where accurate shade matching is essential for achieving optimal restorative outcomes. Color vision deficiency (CVD), a hereditary or acquired disorder that impairs the perception of certain colors, can affect the diagnostic and restorative performance of dental practitioners. Early screening among dental studentscan help identify individuals with CVD and reduce the risk of clinical errors. The aim of study was to determine the prevalence of color vision defects among Bachelor of Dental Surgery (BDS) students at Kathmandu Medical College Teaching Hospital (KMCTH).Methods: A cross-sectional observational study was conducted among BDS students from the first year to internship between April and September 2023. Ethical approval was obtained from the KMC Institutional Review Committee (Ref no: 21032023/05), and informed consent was obtained from all participants. A total of 376 students (98 males and 278 females) were examined using the 24-plateIshihara Pseudoisochromatic Test. Data were entered into Microsoft Excel and analyzed using SPSS software.Results: Of the 376 participants, 17 students (4.52%) were identified with color vision defects. Among them, 13 (3.46%) were males, and 4 (1.06%) were females. Two male students were found to be completely color-blind. Most affected individuals showed mild to moderate CVD, misidentifying one or more Ishihara plates.Conclusion: The prevalence of color vision deficiency among BDS students at KMCTH was 4.52%, with a higher occurrence among males. Regular color vision screening is recommended for dental students and practitioners to identify those with CVD and to ensure accurate color matching and high quality aesthetic outcomes.